Effect of catalyst synthesis of bimetallic nickel-cobalt supported iron-based catalysts on converting palm kernel oil into bio-jet fuel via deoxygenation reaction - Adzahar, Nur Athirah; Alsultan, G. Abdulkareem; Mijan, N. Asikin; Mastuli, M.S.; Lee, H.V.; Yap, Taufiq Yun Hin (Elsevier Ltd, 2025)
Bimetallic nickel-cobalt supported magnetite catalyst has been synthesized using varies techniques such as hydrothermal reactor (R), wet-impregnation (W) and co-precipitation (C) approaches in order to study the effect of preparation methods on the catalytic efficiency of NiCo/Fe3O4 catalyst in transforming the PKO into bio-jet fuel via deoxygenation (DO) reaction. Noted, co-precipitation method rendered greater changes on textural morphological changes, with NiCo/Fe3O4 (C) specific surface area were 157 m2/g followed by Fe3O4 (25 m2/g), NiCo/Fe3O4 (W) (7 m2/g) and NiCo/Fe3O4 (R) (2 m2/g), respectively. Indeed, NiCo/Fe3O4 (C) showed highest weak + strong acidic sites (15,038.1 μmol/g). The efficiency of the DO followed NiCo/Fe3O4 (C) > NiCo/Fe3O4 (W) > NiCo/Fe3O4 (R) > Fe3O4, whereby the highest hydrocarbon yield was 90 % and 21 % is the lowest. Noteworthy to mention, all of the liquid product exhibited selectivity of over 90 % towards the kerosene range. The deoxygenation reaction was optimized using the most effective catalyst, NiCo/Fe3O4 (C) catalyst, through the OVAT technique. The results showed that the optimal conditions were achieved at a temperature of 350 °C within 3 h by using 5 wt% of catalyst loading. The reusability and stability of the NiCo/Fe3O4 (C) catalyst were examined, revealing that the catalyst may be reused for up to 8 runs. During these runs, the catalyst achieved a hydrocarbon yield of up to 55 % and a BJF selectivity of over 95 %. The decrease in the yield and selectivity was attributed to coking, specifically in the form of graphitic carbon.